Restoring Technology and a Seeding Unit for Recovering Mountain Meadow and Pasture Ecosystems - S. M. Dzhibilov; L. R. Gulueva (Сельскохозяйственные машины и технологии)
The paper shows that the constant use of mountain meadows and pastures leads to soil degradation and herbage depletion. It is noted that grass overseeding on the sparse mountain grass meadows and pastures helps to increase their yield and nutritional value. It is revealed that there is a lack of small-sized maneuverable machines capable of grass overseeding in the sparse mountain areas. (Research purpose) To develop and manufacture a laboratory model of a block module aggregated with the Feng Shou 180 mini-tractor for surface grass overseeding, to ensure an accelerated increase in the perennial grass yield and soil resistance to water and wind erosion. (Materials and methods) The restoring technology was substantiated and a laboratory block module was developed for sowing legumes and cereals. The seeding unit and technology were tested in the mountainous zone of the Republic of North Ossetia-Alania at a 1540-meter altitude above sea level. Grasses were overseeded on a sparse section of a 13-16-degree steep northern slope in the area of Sugsadtanrag. The technical examination of the unit was carried out in accordance with the agrotechnical requirements and terms of reference. The surface application of grass seeds was performed according to the norms. (Results and discussion) A laboratory block module aggregated with the Feng Shou 180 mini-tractor for surface grass overseeding was produced. It is established that the laboratory model of the unit complies with the agrotechnical requirements and terms of reference. (Conclusions) It is found that within the second year of using the unit, there was a 90-170 percent increase in the herbage yield and a certain improvement in the botanical composition, which positively affected the feed quality. The use of the developed block-module is proved to be reasonable and helpful in mountain meadows and pastures having 16-degree steep slopes.